Synthesis and performance evaluation of low-molecular-weight biobased polyester rubber as a novel eco-friendly polymeric plasticizer for polyvinyl chloride - Zhang, Qinan; Sun, Jiahui; Yao, Zehao; Ding, Xuejia; Wang, Zhao; Zhang, Liqun (Frontiers in Materials, 2024)
Developing eco-friendly polymeric plasticizers with excellent migration resistance is one of the research hotspots in the polyvinyl chloride (PVC) industry. A low-molecular-weight biobased polyester rubber (LMW-BPR) was synthesized from five biobased polyester monomers in a 100-L reactor and evaluated as a potential ecofriendly polymeric plasticizer for PVC. The obtained LMW-BPR is an amorphous polyester material with a low glass transition temperature of -48 o C and a molecular weight of 22 kg/mol, which is lower than that of existing polyester rubber but higher than those of most polyester plasticizer commodities. Plasticized PVC composites with a total plasticizer content of 50 phr were prepared by using the mixture of LMW-BPR and di-isononyl cyclohexane-1,2-dicarboxylate (DINCH, an eco-friendly monomeric plasticizer commodity) as the plasticizer. The migration resistance test showed that the migration loss of plasticizer in plasticized PVC composite decreased significantly with the increase of LMW-BPR content. When the content of LMW-BPR reaches 30 phr, the plasticized PVC composites are almost nonmigratory. In addition, compared with PVC composite plasticized by pure DINCH, co-plasticized PVC composites containing LMW-BPR exhibit higher tensile strength and thermal stability, and their flexibility, low-temperature resistance and biocompatibility are also maintained at a similar level to the former. Overall, LMW-BPR is an effective eco-friendly polymeric plasticizer for PVC and also sustainable and scalable, thus it is worthy of wide application.